2006
DOI: 10.1038/nature05126
|View full text |Cite
|
Sign up to set email alerts
|

Structure of eEF3 and the mechanism of transfer RNA release from the E-site

Abstract: Elongation factor eEF3 is an ATPase that, in addition to the two canonical factors eEF1A and eEF2, serves an essential function in the translation cycle of fungi. eEF3 is required for the binding of the aminoacyl-tRNA-eEF1A-GTP ternary complex to the ribosomal A-site and has been suggested to facilitate the clearance of deacyl-tRNA from the E-site. Here we present the crystal structure of Saccharomyces cerevisiae eEF3, showing that it consists of an amino-terminal HEAT repeat domain, followed by a four-helix b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
174
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(188 citation statements)
references
References 47 publications
14
174
0
Order By: Relevance
“…14,26,30,31,47,69,71 One of the key features differentiating eukaryotic from prokaryotic ribosomes is the extent of protein-protein interactions on the ribosome surface. It is believed that this structural complexity is directly related to the evolution of the translation apparatus, including appearance of new translation factors and multiple sophisticated mechanisms of translation control that are absent in prokaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,26,30,31,47,69,71 One of the key features differentiating eukaryotic from prokaryotic ribosomes is the extent of protein-protein interactions on the ribosome surface. It is believed that this structural complexity is directly related to the evolution of the translation apparatus, including appearance of new translation factors and multiple sophisticated mechanisms of translation control that are absent in prokaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…70 eEF3 binds near the E-site and is necessary for clearance of the deacylated tRNA from the ribosome. 70,71 Cryo-EM analysis of the eEF3-80S complex (at 9.9A ) showed that the factor binds near the head of the 40S ribosomal subunit and makes contacts with both the 40S and 60S subunits. 71 The so-called HEAT domain of eEF3 was mapped to interact with eukaryote-specific extensions of uS13 and 2 protein-rich regions (unassigned due to low resolution) termed rpSX1 and rpSX2.…”
Section: Interaction Of 40s Ribosomal Proteins With Eef3mentioning
confidence: 99%
See 2 more Smart Citations
“…Research by many colleagues and ourselves extended this analysis to complete ABC proteins (e.g., Lamers et al , 2000 ;Obmolova et al , 2000 ;Locher et al , 2002 ;Andersen et al , 2006 ;Dawson and Locher , 2006 ;Lammens et al , 2011 ;Lim et al , 2011 ), and there is now a good understanding of the principal architecture and ATP-dependent structural dynamics of a variety of ABC proteins ( Figure 1A). A pair of NDBs undergoes conformational cycles by ATP driven engagement and disengagement, which impacts on the structure and substrate binding properties of the NBDs and its function-specific associated domains.…”
Section: Abc Enzymes: Versatile Molecular Machines or Switchesmentioning
confidence: 99%